O Ensino de Microbiologia nas escolas como forma de prevenção de doenças infecciosas: uma análise crítica do currículo paulista - Paula, Fernanda (Universidade Federal de São Carlos, 2022)
Microbiology is the science devoted to the study of microscopic organisms, such as bacteria, fungi, protozoa and viruses, and their biological activities. As development of microbiology it was discovered that microorganisms are related to the cause of infectious diseases and, as a form of prevention, there was a need to improve basic sanitation and hygiene conditions. Still Today, infectious diseases are a public health problem in Brazil and It is extremely important to reinforce prevention measures, based on policies public. Thus, schools play a key role in promoting hygiene education and other disease prevention measures. the teaching of microbiology is already present in basic education in the disciplines of Science and biology, and can be further explored with the specific objective of preventing infectious diseases. However, so that the teaching of microbiology does not become abstract for the students, it is necessary that the teaching-learning process be significant. Thus, this work aimed to carry out an analysis critique of microbiology skills, with an emphasis on teaching diseases infectious diseases, present in the Paulista Curriculum and in the support materials, “Curriculum in Action”, made available by the State of São Paulo to students and teachers of the public network. In addition, a bibliographic survey of alternative methodologies for teaching microbiology in basic education, with the objective of proposing didactic activities to facilitate and improve the quality of the teaching-learning process, making the teaching of microbiology a effective way to promote the prevention and knowledge of infectious diseases.
Teaching Microbiology in schools as a way of Infectious disease prevention: a critical analysis from the São Paulo curriculum
Keywords: Microbiologia; Doenças Infecciosas; Metodologias de Ensino; Currículo Paulista; Microbiology; Paulista Curriculum; infectious diseases; teaching methodologies; CIENCIAS HUMANAS::EDUCACAO::CURRICULO